Peran Linguistik Forensik terhadap Penegakan Hukum Indonesia: Studi Analisis Ujaran Kebencian Suku Lampung - Marhaban Istiqama Ode; Nailil Huda (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2022)
Language and linguistics as a means of communication have now touched the realm of law and justice known as forensic linguistics. As a field that is closely related to the enforcement of justice, forensic linguistics only provides signals that can reveal the truth that will lead to justice. This paper aims to determine the role of forensic linguistics in law enforcement in Indonesia, especially in the field of language through a case study of Lampung ethnic hate speech. The method used is a qualitative method with a descriptive analysis approach. The results of data analysis showed that 1) UM made hate speech intentionally to the Lampung tribe in particular by using a choice of words that had a negative meaning; and 2) UM made an invitation to the public to exterminate the Lampung tribe in the second sentence which was delivered in writing on its social media account.